Aphorisms and Short Literary Works in a Stylistic-Cognitive Perspective: Some Surveys between Poetry and Prose (ENTHYMEMA, 2025)
This article examines the stylistic characteristics of short aphoristicwritings, taking into account the acquisitions of cognitive poetics. We reflect onthe reasons why short communication has now taken full autonomy, especially insocial media, compared to elaborate, literary or even essayistic or journalisticcommunication. Some examples of analysis are then provided, both in poetry(Valentino Zeichen) and in prose (Carla Vasio).
Keywords: Aphorism; Brevitas; Cognitive Poetics; Valentino Zeichen; Carla Vasio